What Drives the Impact of Corporate Governance on Firm Value? Evidence from Earnings Management at Indonesian Sharia Stock Index (ISSI) - Erdin Maulana Tristianto; Ridha, M. Arsyadi (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2023)
Purpose: This study sought empirical evidence on the impact of corporate governance as proxied by the board of commissioner's size, managerial ownership, and audit quality on firm value using earnings management as an intervening variable in energy sector companies indexed by the ISSI and listed on the Indonesia Stock Exchange from 2014 to 2022. Methodology: This study uses purposive sampling technique and panel data, resulting in 171 selected sample data units that will be processed using eviews. Findings: Managerial ownership, audit quality, and earnings management all have a significant and beneficial impact on firm value. However, the board of commissioners has a negative impact. Aside from that, the board of commissioners's size and managerial ownership do not affect earnings management, but audit quality has a negative effect. Earnings management as an intervening variable influences corporate governance variables. Novelty: This research attempts to provide a novel viewpoint on how political instability in a country can affect the investment climate in the Indonesian energy sector, which has received little attention previously. This study also acknowledges the inconsistency of previous research findings regarding the relationship between corporate governance and firm value, paving the way for incorporating earnings management variables as mediators and ultimately contributing to our understanding of the complex dynamics between these elements.